Analisis Prinsip Etika Penelitian sebagai Landasan Moral dalam Karya Ilmiah: Perspektif Etika Akademik di Perguruan Tinggi Indonesia - Hidayati, Zulfa Rahmat; Jailani, Syahran; Risnita (MAN 4 Kota Pekanbaru, 2025)
Research ethics serve as the moral foundation of scholarly work, emphasizing integrity, honesty, and social responsibility in producing authentic and beneficial research. However, ethical violations persist among academics due to factors such as easy access to information that promotes careless plagiarism, pressure to publish, inadequate competence, and limited understanding of ethical principles. This uneven awareness of ethical values highlights the need for continuous reinforcement. Using a qualitative approach and literature review method, this article examines the core principles of research ethics, researchers’ codes of conduct, common ethical violations, and strategies to strengthen ethical awareness. The findings reveal that consistent application of ethical standards requires clear regulations, structured training, and a sustained culture of integrity. Ultimately, research ethics should not be viewed merely as formal compliance, but as intrinsic moral values that define the identity of a responsible and professional researcher.